THE EFFECT OF TRAINING TECHNOLOGIES ON THE CHANGES IN THE COMMUNICATIVE COMPONENT OF THE PSYCHOLOGICAL AND PEDAGOGICAL COMPETENCE OF POTENTIAL FOSTER PARENTS - Pavlovna Kondratyeva, Natalia; Alexandrovna Kechina, Marina; viktorovna Savinova, Tatyana; Alexandrovna Vdovina , Natalia (Revista Inclusiones, 2019)
The study aims to determine the distinct features of the communicative component of the psychological and pedagogical competence of potential foster parents, as well as to detect the impact training sessions have on changes in this component. The experimental study included the confirmatory stage, the design stage, the program approbation for the psychological training, and the control stage. The study sample included 48 potential foster parents. The main study methods included theoretical, experimental, diagnostic, and statistical methods. The article highlights the distinct features of sociability, empathy, and style of behaviour in a conflict in potential foster parents. The main aspects and approbation results for the training for the development of the communicative component of the psychological and pedagogical competence of potential foster parents are also presented. The proof is provided for the idea that the implementation of the specifically developed training program that includes exercises aimed to develop flexibility, empathy, and ability to establish contacts and competently build relationships helps to develop the communicative component of psychological and pedagogical competence of potential foster parents. Materials in the article present practical value for psychologists in social services.